ENHANCING ACCOUNTABILITY IN BUSINESS FUND MANAGEMENT: BUDGET PREPARATION TRAINING FOR INDRAMAYU MSMEs TO SUPPORT SDG 8 IN THE ERA OF GLOBAL COMPETITIVENESS - Ulupui, I Gusti Ketut Agung; Utaminingtyas, Tri Hesti; Nindito, Marsellisa; Haryani, Putri; Utami, Karin; Bassae, Ridho Rambu; Wei, Andrew Saw Tek (International Journal of Engagement and Empowerment (IJE2), 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indramayu face significant challenges related to limited capital and financial literacy, hindering their ability to effectively manage business funds and access necessary financing. This community engagement program aims to enhance the financial literacy and accountability of MSME owners in Indramayu through a budget preparation training program. In collaboration with international partners from Universiti Malaysia Sabah, the program focused on providing practical training on financial management, including budgeting, cash flow management, and financial record-keeping. The initiative aligns with Sustainable Development Goal (SDG) 8, promoting inclusive and sustainable economic growth by improving the business practices of MSMEs. The program successfully improved participants' understanding of basic financial reporting and budgeting, with significant improvements in their ability to manage business funds using digital tools. By equipping MSMEs with the necessary skills, this initiative contributes to enhancing the competitiveness and sustainability of local businesses in a globalized market.